HIX, Simon y HOYLAND, Bjorn (2012). Sistema político de la Unión Europea. Madrid: McGraw-Hill (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2012)
Recensión de la obra: HIX, Simon y HOYLAND, Bjorn (2012). Sistema político de la Unión Europea. Madrid: McGraw-Hill.